To simplify the expression, we will distribute the 3/4 to the terms inside the parentheses:
-5 + 3/4(8h + 12) - 10h
= -5 + (3/4)(8h) + (3/4)(12) - 10h
= -5 + (24/4)h + 9 - 10h
= -5 - 10h + (24/4)h + 9
= (-10h + (24/4)h) - 5 + 9
= -10h + (6h) - 5 + 9
= -4h + 4 - 5 + 9
= -4h + 8
So, the simplified expression is -4h + 8.
Simplify −5+3/4(8h+12)−10h .
5 answers
wrong
You're right, I made a mistake. Let's correct it:
To simplify the expression, we will distribute the 3/4 to the terms inside the parentheses:
-5 + 3/4(8h + 12) - 10h
= -5 + (3/4)(8h) + (3/4)(12) - 10h
= -5 + (24/4)h + 36/4 - 10h
= -5 + 6h + 9 - 10h
= 6h - 10h - 5 + 9
= -4h - 4 + 9
= -4h + 5
So, the simplified expression is -4h + 5.
To simplify the expression, we will distribute the 3/4 to the terms inside the parentheses:
-5 + 3/4(8h + 12) - 10h
= -5 + (3/4)(8h) + (3/4)(12) - 10h
= -5 + (24/4)h + 36/4 - 10h
= -5 + 6h + 9 - 10h
= 6h - 10h - 5 + 9
= -4h - 4 + 9
= -4h + 5
So, the simplified expression is -4h + 5.
also wrong
My apologies for the error. Let's try simplifying the expression again:
-5 + 3/4(8h + 12) - 10h
= -5 + (3/4)(8h) + (3/4)(12) - 10h
= -5 + (3/4)(8h) + 9 - 10h
= -5 + 6h + 9 - 10h
= (6h - 10h) + (-5 + 9)
= -4h + 4
So, the simplified expression is -4h + 4.
-5 + 3/4(8h + 12) - 10h
= -5 + (3/4)(8h) + (3/4)(12) - 10h
= -5 + (3/4)(8h) + 9 - 10h
= -5 + 6h + 9 - 10h
= (6h - 10h) + (-5 + 9)
= -4h + 4
So, the simplified expression is -4h + 4.